Thyroid Hormone Concentrations in Dialysate During Hemodialysis in Children - Waters, W.; Bulla, M.; Buschsieweke, U.; Kutzim, H. (Nuklearmedizin - NuclearMedicine, 1981)
Thyroxine (T4) concentration in dialysate in the course of hemodialysis was determined in 15 children. Concentrations were measured by a modified radioimmunoassay. During hemodialysis there was a slight increase in T4 concentration. At the end of hemodialysis T4 concentration was about 50% higher than soon after the onset of hemodialysis. The loss of T4 into dialysate during hemodialysis was 19.2 μg; the loss of T3 was less than 75 ng. The amount of the daily loss of thyroid hormones into dialysate was found to be in the range of normal urinary excretion. The lowering of serum thyroid hormone concentrations in children on hemodialysis cannot be explained by the loss of these hormones into dialysate.